The association of physical activity with intrinsic capacity: findings from longitudinal analysis in CHARLS and HRS - Xiaoxian Yang; Yan Zhuang; Hui Huang (Aging Clinical and Experimental Research, 2026)
Abstract Background Physical activity (PA) is a pivotal modifiable determinant of intrinsic capacity (IC), a core component of healthy aging. Aims This study aimed to examine the association between PA and the risk of IC impairment among middle-aged and older adults using nationally representative cohorts from China and the United States. Methods Data from CHARLS (2011–2015) and HRS (2010–2018) were used, including 781 and 2,601 participants, respectively. PA was quantified by metabolic equivalents (MET), and IC impairment was defined as dysfunction in one or more of five domains. Cox proportional hazards regression, restricted cubic splines (RCS), subgroup analysis and nomograms were used for statistical analysis. Results PA was inversely associated with the risk of IC impairment in both cohorts. In CHARLS, low and moderate PA significantly reduced IC impairment risk [Hazard Ratio (HR) = 0.691, 0.687; P < 0.05), while high-intensity PA had no significant effect. In HRS, all PA levels were protective (HR = 0.720, 0.736, 0.739; P < 0.05). RCS showed non-linear dose-response relationships between PA and IC impairment risk. Subgroup analysis indicated the protective effect of PA was consistent in CHARLS, but modified by marital status in HRS (only significant in married people). The nomograms showed modest discriminative ability [Area Under the Curve (AUC) > 0.6]. Discussion The protective association between PA and IC impairment varied by cohort and PA intensity. Conclusion PA was associated with a reduced risk of IC impairment, supporting targeted PA-based interventions for healthy aging. Trial registration Not applicable.